MODEL EPIDEMIK SEIR PADA KASUS PENYAKIT JANTUNG KORONER PADA PENDERITA KOLESTROL - Afifah Farhanah Akadji; Karina Anselia Mamonto; Anisa Fitra Dila Hubu; Mohamad Syahfwan Ismail (Universitas Negeri Gorontalo, 2020)
Coronary heart disease (CHD) is caused by various reasons. One of the main causes of coronary heart disease is cholesterol. Cholesterol comes from two sources, namely, that which is produced by the liver and through the food consumed. This article discusses the mathematical model of coronary heart disease which refers to the SEI (Susceptible-exposed-infected) model, with modifications in the form of the addition of the recovered (R) variable and parameters in the form of a healthy lifestyle and surgery. Hereinafter this model is called the SEIR (Susceptible-Exposed-Infected-Recovered) model. This study aims to determine the problem of coronary heart disease in cholesterol sufferers and to analyze the effect of operating parameters and a healthy lifestyle on the patient's healing (R) is higher than the opportunity value of the other groups. And the opportunity value of an infected individual is much lower than that of other groups. This shows that the chances of recovery for people with coronary heart disease with a high operating route.